Workload analysis of medical record and health information officers at a hospital - Sonia, Dina; Fannya, Puteri; Putra, Daniel Happy (International Journal Of Community Medicine And Public Health, 2024)
Background: This research aims to analyze the workload of medical record and health information officers at hospital X. Initial observations identified several issues, such as frequent multitasking by staff, an imbalance in task distribution, leading to delays in completing tasks within the stipulated time. Methods: The research method used is a case study with a qualitative approach. The data collection techniques used include observation and interviews. Results: The calculating of the workforce needed for medical record and health information officers at hospital X based on workload analysis, shows that 29 officers are required, but only 20 are currently available, indicating a shortage of 9 peoples. Conclusions: The findings of this research are expected to aid hospital management in making decisions to either recruit more officers or adopt technology to automate work processes, thereby reducing staff workload.